Solid Pseudopapillary Neoplasms Are Rare, Indolent Pancreatic Tumors in Young Women - Amin Dalili; Mohsen Aliakbarian; Mehdi Karimi-Shahri; Alireza Samadi; Sara Raji (Case Reports in Surgery)
Introduction. Solid pseudopapillary neoplasm (SPN) is a rare and indolent pancreatic tumor with low malignant potential which frequently occurs in reproductive-age females. Complete resection is almost always the curative option. Case Presentation. We present a 20-year-old woman with acute epigastric pain and vomiting in multiple episodes. Abdominal ultrasound showed a hypoechoic lesion with the probable source in the pancreas. Following that, CT scans and Endoscopic Ultrasound (EUS) manifested a 9×7.5 cm-sized hypodense mass with heterogeneous well-defined margins in the pancreas suggesting the diagnosis of SPN. Whipple’s procedure was performed. Histopathological examination and immunohistochemistry confirmed SPN without evidence of malignancy. Discussion. SPN is known as a tumor with a favorable prognosis and a long survival rate after complete resection. However, some literature focused on minimally invasive surgery as an alternative surgical approach.